COMPLEX TREATMENT OF PATIENTS WITH RECTAL MALIGNANT TUMOR WITH LONG-TERM USE OF ENDOLYMPHATIC AND REGIONAL POLYCHEMOTERAPY - Uktam M. Kurbankulov; Munira X. Norbekova; Azizbek F.Valijonov; Shirina A. Valijonova (Scholar Express Journals, 2023)
In recent decades, in many countries of the world there has been an increase in the incidence of malignant tumors of the rectum (MTR). Incidence statistics per 100,000 population in different countries of the world are not the same: 33.2 in the USA, 17.8 in Sweden; -25.8 in UK; -15.7 in Japan; In Senegal, 2.5. In Russia, the incidence of a malignant tumor of the rectum (MTR) also has a pronounced upward trend: the overall increase in incidence over the past decade is 37.4%. The incidence reaches -12.6 in women and -12.5 in men per 100,000 population. Incidence rates of malignant tumors of the rectum among men vary significantly across the CIS countries. Thus, in Turkmenistan, Uzbekistan and Armenia it ranges from 3.0 to 3.5; And in Russia and Belarus it reaches 11.3-14.8. For women in Turkmenistan, Uzbekistan and Armenia, this figure is higher than 2.5, while in Russia and Belarus this figure is -7.6-8.2. In 2005, 1.9 cases of a malignant tumor of the rectum per 100,000 population were detected in Uzbekistan, and this pathology ranks eighth in the structure of the overall incidence. The global standard for mortality from MTR was 7.4, in Europe -11.1, where the mortality rate for men was 9.6 and 14.4, and for women - 5.5 and 8.1, respectively
Keywords: Endolymphatic; regional polychemotherapy; RC